RETRACTED: The Effect of Work Motivation, Work Experience, Work Compensation and Work Discipline on Employee Productivity of PT. Easypower Global Technology - Jody Eko Saputra; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science, 2024)
In order to anticipate the era of globalization which is marked by an increasingly competitive business world and no longer recognizes national boundaries, companies are required to optimize all available resources. This study aims to determine the impact of work motivation, work experience, work compensation and work discipline on the work productivity of PT. Easypower Global Technology. This research was conducted on 106 respondents, namely employees of PT. Easypower Global Technology. In taking the sample for this research, the method used is the random sampling method. The data analysis technique used was multiple linear regression analysis and the hypothesis test used was the T-statistical test which was processed on SPSS version 22. The results showed that the independent variables simultaneously or together had a significant effect on the dependent variable. The results of the calculation of the F test showed that Fcount Ftable (101.482 2.46). Likewise, the results of the T-test state that tcount ttable and the significance value of (0.05), which means that the independent variable partially has a significant effect on the dependent variable. It can be concluded that, Work Motivation, Work Experience, Work Compensation and Work Discipline simultaneously or partially have a significant effect on the Work Productivity of PT. Easypower Global Technology.